Didactic autonomy of a geography teacher in the context of developing students’ spatial thinking - Yemchuk, Tetiana (Educological discourse, 2026)
The article presents a theoretical and pedagogical analysis of the didactic autonomy of a geography teacher as a key pedagogical condition for the development of students’ spatial thinking within the framework of the New Ukrainian School reform. The relevance of the study is determined by the contradiction between the increasing standardization of general secondary education curricula and the need for flexible pedagogical interpretation aimed at achieving competency-based learning outcomes. Based on the synthesis of contemporary pedagogical research and regulatory educational documents, an authorial definition of the concept of “didactic autonomy of a geography teacher” is proposed. Didactic autonomy is interpreted as an integrated professional and pedagogical characteristic that enables teachers to independently select, adapt, and combine the content, methods, forms, and instructional tools of teaching to effectively develop students’ spatial thinking in accordance with educational standards and learners’ needs. A structural model of didactic autonomy is substantiated, including content-related, methodological, organizational, and evaluative-reflective components, whose interaction ensures the implementation of activity-based and inquiry-oriented approaches in geography education. The empirical component of the study is based on a questionnaire survey of geography teachers in general secondary education institutions. The results indicate that a higher level of didactic autonomy is associated with more frequent use of research-based, project-oriented, and local geography methods, which contribute to the development of spatial analysis skills. At the same time, the application of geoinformation technologies and field research remains limited due to material, technical, and organizational constraints. The practical significance of the research lies in the possibility of applying its findings in methodological support for geography teachers, professional development programs, and further elaboration of didactic models that enhance teacher autonomy as a factor in improving the quality of geography education and fostering students’ spatial thinking.